Keep'em motivated : a practical guide to motivating employees - Williams, Larry R. (Singapore : Times Editions, 2003)
Annotation The ideal guide to learning to be a motivating leader and discover how to inspire and bring out the best in others at the same time. Learn to motivate others and be motivated in the process! In this book, readers will find: 14 solutions on motivating employees in the cyber age, including the latest thinking on motivation; 13 short and informative'Motivation in Action' stories, from places such as Singapore, Malaysia, Japan and the United States; 12 self-improvement assessments designed to guide personal growth and new learning; 70 websites on motivation to further knowledge; timely quotations from Buddha, Dale Carnegie, Confucius, Peter Drucker, Gandhi, various proverbs, and many more...
Keywords: Employee motivation